Institutions and the Allocation of Entrepreneurial Talent between Productive and Destructive Activities - Mark Sanders; Utz Weitzel (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2009)
Entrepreneurship is generally regarded as a force of change, innovation and development in modern economies. Entrepreneurs bring new and better products to markets, restore allocative efficiency through arbitrage and reinvest their profits. However, as Baumol (1990), Mehlum et al. (2003) and Acemoglu (1995) have argued, the same energy and talent can also be allocated to unproductive ends and reduce total welfare. In this paper we present a model that analyzes the allocation of a given entrepreneurial talent over destructive and productive activities. We show that in this model two stable equilibria can emerge. As Baumol (1990) hypothesized, institutions determine the pay-offs to both types of entrepreneurial activity and hence drive this allocation. But we also show that the distribution of initial wealth and entrepreneurial talent plays a decisive role. This analysis provides a different perspective on the importance of high quality institutions in developing countries and sheds light on the situation in conflict and post-conflict countries, where both informal and formal institutions arguably have broken down. Under such circumstances, our analysis shows that micro credits can support the transition to a productive equilibrium, because they help to overcome credit contraints without creating incentives for destructive entrepreneurship.
Keywords: 330; growth; development; entrepreneurship; innovation; occupational choice